B.J. Habibie’s Political Thought in Democratization in Indonesia - Ahmad Depri Kurniawan; Didik Sukriono; Rosyid Al Atok (Journal of Politics and Policy, 2021)
This study aims to describe BJ. Habibie’s political thought in democratization in Indonesia. This study uses a qualitative approach with library research type. Data collecttion tehnique used in this study is a research tehnique using the domumentation method. Data analysis using content analysis. The result of study show that BJ. Habibie’s political thought began to appear when he became the president of Rebublic Indonesia, where these thought were embodied in his policies. Several policies of the presiden BJ.  Habibie during his reign included: (1) economic reform; (2) restoration of political legitimacy; (3) the fisrt amendment to the 1945 constitution; (4) democratization of the press and human right enforcement; and (5) the East-Timor referendum.  The role of BJ. Habibie in democratization in Indonesia can be seen from hos leadership style which changes the authoritarian leadership style of presiden Soeharto to be more democratic such as the release of political prisoners, freedom of the press, freedom to express opinions in public and many more.